THE EFFECT OF OSILATION AND WAVE ANIMATION TOWARD STUDENT’S PHYSIC LEARNING ACHIEVEMENT - Rulyati, Neneng; Ahzan, Sukainil; Fuaddunazmi, M. (Lensa : Jurnal Kependidikan Fisika, 2016)
This research was aimed at find out the effect of using vibration animation and swell toward students physics in academic year 2015/2016. This research was experimental research. The population in the research is all of the students VIII SMP Negeri 3 Monta Bima. The researcher uses cluster random sampling for took the sample, those were took two class VIIIA as experimental class, and VIIIB as control class. The result in this research used normality uses SPSS 17 was significant > 0,05 in succession was 0,185 and 0,033 for experimental class, although for  control class was 0,173 and 0,023. Although the result of homogenytas experimental class was 3,263 and control class was 1,831. Based on the test result SPSS 17 by using test T-test provided the value of T count it  1.498 with the standard of significant 0,151 for class experimental, as for the control T count it  2.172 with the standard of significant 0,041. And so what happen is T count it  < T table. So Ho rejected and Ha accepted. Therefore can be concluded that there is vibration animation and swell have significant effect in learning students physics SMP Negeri 3 Monta Bima academic year 2015/2016.